White privilege and male privilege: A personal account of coming to see correspondences through work in women's studies - McIntosh, Peggy (Wellesley College, Center for Research on Women, 1988)
Through work to bring materials and perspectives from Women's Studies into the rest of the curriculum, I have often noticed men's unwillingness to grant that they are overprivileged in the curriculum, even though they may grant that women are disadvantaged. Denials that amount to taboos surround the subject of advantages that men gain from women's disadvantages. These denials protect male privilege from being fully recognized, acknowledged, lessened, or ended.
https://www.wcwonline.org/Fact-Sheets-Briefs/white-privilege-and-male-privilege-a-personal-account-of-coming-to-see-correspondences-through-work-in-women-s-studies-2
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; discours dominant; intersectionnalité; privilèges; périodes historiques; racisme; ressource en ligne; régions géographiques; savoir expérientiel; sexisme; systèmes d'oppressions; états-unis

Une femme - Ernaux, Annie (Gallimard, 1987)
Annie Ernaux s'efforce ici de retrouver les différents visages et la vie de sa mère, morte le 7 avril 1986, au terme d'une maladie qui avait détruit sa mémoire et son intégrité intellectuelle et physique. Elle, si active, si ouverte au monde. Quête de l'existence d'une femme, ouvrière, puis commerçante anxieuse de «tenir son rang» et d'apprendre. Mise au jour, aussi, de l'évolution et de l'ambivalence des sentiments d'une fille pour sa mère : amour, haine, tendresse, culpabilité, et, pour finir, attachement viscéral à la vieille femme diminuée. «Je n'entendrai plus sa voix... J'ai perdu le dernier lien avec le monde dont je suis issue.
Section: 105 pages ; 18 cm.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; approches et analyses; care; classisme; cours; discipline; europe; famille; france; inégalités; lit301N; littérature; maternité; premier cycle; privilèges; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*